2023
DOI: 10.1186/s42358-023-00323-1
|View full text |Cite
|
Sign up to set email alerts
|

Risk factors of systemic lupus erythematosus: an overview of systematic reviews and Mendelian randomization studies

Xin-Yu Xiao,
Qian Chen,
Yun-Zhou Shi
et al.

Abstract: Background The etiology of systemic lupus erythematosus is complex and incurable. A large number of systematic reviews have studied the risk factors of it. Mendelian randomization is an analytical method that uses genetic data as tool variables to evaluate the causal relationship between exposure and outcome. Objective To review the systematic reviews and Mendelian randomization studies that focused on the risk factors of systemic lupus erythematos… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 88 publications
0
2
0
Order By: Relevance
“…Confounders were manually retrieved from previous studies in PubMed database. [24–26] The PhenoScanner V2 database (http://www.phenoscanner.medschl.cam.ac.uk/) was used to screen and exclude SNPs associated with confounders.…”
Section: Methodsmentioning
confidence: 99%
“…Confounders were manually retrieved from previous studies in PubMed database. [24–26] The PhenoScanner V2 database (http://www.phenoscanner.medschl.cam.ac.uk/) was used to screen and exclude SNPs associated with confounders.…”
Section: Methodsmentioning
confidence: 99%
“…Multivariate MR analysis was performed to determine whether lifestyle factors, dietary factors, and exercise played important roles in the causal effect of lipid-lowering drugs on SLE risk. According to previous reviews on SLE risk ( Vordenbäumen et al, 2023 ; Xiao et al, 2023 ), we identified smoking status and alcohol intake frequency as the first group of lifestyle factors, selenium and iron intake as the second group of dietary factors, and accelerometer-based physical activity measurement as the third group of physical activity-related factors. Data for the three groups of factors were obtained from the UK Biobank.…”
Section: Methodsmentioning
confidence: 99%
“…The global prevalence of SLE is 43.7 (ranging from 15.87 to 108.92) per 100,000 persons, with much higher rates among Asians, Hispanics and Africans [ 105 ]. The pathogenesis of SLE is complex, involving many risk factors including diseases (e.g., atopic dermatitis), lifestyle choices (e.g., smoking and drinking), and genetic polymorphisms (e.g., genes related to B cell and T cell functions) [ 106 ]. SLE can damage tissues and organs in the body, leading to various complications such as lupus nephritis (LN) [ 107 ].…”
Section: Introductionmentioning
confidence: 99%